2023
DOI: 10.3390/rs15030690
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Methods for Distinguishing Glacier Zones Using Satellite SAR Data

Abstract: Changes in glacier zones (e.g., firn, superimposed ice, ice) are good indicators of glacier response to climate change. There are few studies of glacier zone detection by SAR that are focused on more than one ice body and validated by terrestrial data. This study is unique in terms of the dataset collected—four C- and L-band quad-pol satellite SAR images, Ground Penetrating Radar data, shallow glacier cores—and the number of land ice bodies analyzed, namely, three tidewater glaciers in Svalbard and one ice cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…GMM is a probabilistic-based clustering method [34], which is computed by iterative optimization using the expectation maximization (EM) algorithm [35]. The EM algorithm is an iterative approach to solving a special maximum likelihood problem.…”
Section: Gaussian Mixture Modelmentioning
confidence: 99%
“…GMM is a probabilistic-based clustering method [34], which is computed by iterative optimization using the expectation maximization (EM) algorithm [35]. The EM algorithm is an iterative approach to solving a special maximum likelihood problem.…”
Section: Gaussian Mixture Modelmentioning
confidence: 99%
“…Due to the simple structure and easy implementation of Gaussian distributions, the Gaussian mixture model (GMM) is commonly used for statistical modeling in image segmentation [17]. For example, Bao et al [18] proposed a water extraction algorithm in SAR images, and GMM was used for the statistical modeling of targets and backgrounds based on the initial extraction of homogeneous regions using the Otsu algorithm; Liu et al [19] used Generalized GMM to achieve change detection based on the segmentation of different images; Barzycka et al [20] tested and validated GMM-based methods for extracting glacier zones, and the result indicated that the GMM-EM (Expectation maximization) method was suitable for extracting glacier zones based on sigma0 and Pauli decomposition of SAR images. Moreover, GMM can also be applied to domain adaptation research in machine learning [21].…”
Section: Introductionmentioning
confidence: 99%